Analysing The Impact Of Social Media Marketing On Guests Hotel Selection (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Hotel guests are ultimately seeking the best qualities to receive satisfactory  and comfortable facilities during their stay and how internet and technology has  fundamentally changed guests behaviour and their decision making processes for  accommodation selection. In this era of digital development in technology guest have access  to information through communication channels that are very much available at fingertips.  Thus, the present study focuses on analysing the impact of social media marketing on guest’s  hotel selection for a comfortable and satisfactory stay. Objectives: The objectives of the  study were identification of social media marketing tools used by the different hotels and the  impact of social media marketing on guest’s selection of hotel. Methodology: The  questionnaire was distributed through Google Forms and responses were collected from 120  respondents from the state of Uttar Pradesh and Madhya Pradesh. Results: Most influential  features on social media marketing in Guests selection of Hotel with 48% of responses are  Location of the hotel (country, city, place etc.), Online Reviews & Feedback (40%) and  Unique Selling Proposition of the hotel with 37% of responses (Special features).  Conclusion: Social media marketing plays a pivotal role for hotels and business to build  trust and establish credibility with their guests. In today’s scenario and age, it is a common  tool for guests to research about hotels while choosing an accommodation and this is the  reason, why social media marketing tools are so important.
Keywords: Social Media Marketing; Hotel; Guest; Selection